PENGARUH INVESTASI DAN KONSUMSI TERHADAP PENYERAPAN TENAGA KERJA PADA SEKTOR INDUSTRI PENGOLAHAN DI KOTA KENDARI - Kadir, Kadir; Rahim, Manat; Suriadi, La Ode (JURNAL EKONOMI UHO, 2016)
The objective of this study is to examine the de terminants of labor absorption in manufacture sector at Kendari City.  This  study used panel data  comprising 6 districts at Kendari City  in the period  2009-2013 including fixed effect model.  The  results showed that investment  have positive  effect on employment, while consumption have negative  effect. The higer of investment the lower labor absorption in manufactures industry. This imply, when   investment increasing, manufactures sector is labor saving